Using Tiktok Application for English Vocabulary Mastery of Seventh Grade Students - Saputri, Rifka Kurnia; Samtidar, Samtidar; Aeni, Nur (Pascasarjana Universitas Negeri Makassar, 2026)
This study examined the effect of using TikTok on improving vocabulary mastery among seventh-grade students. A quantitative approach with a pre-experimental design was employed, involving 31 students selected through random sampling. Vocabulary mastery was assessed through pre-test and post-test instruments focusing on three aspects: pronunciation, spelling, and meaning. Prior to the treatment, a pre-test was administered to measure students’ initial vocabulary ability. The treatment was conducted in four instructional meetings by integrating TikTok videos into vocabulary learning activities, followed by a post-test to measure students’ progress. The results indicated a significant improvement in students’ vocabulary mastery after the implementation of TikTok. The mean score increased from 71.45 in the pre-test to 89.19 in the post-test. The N-Gain score reached 0.66, categorized as moderate improvement. Further analysis using a paired sample t-test revealed a statistically significant difference between pre-test and post-test scores (p < 0.05), indicating that the use of TikTok had a positive effect on students’ vocabulary mastery. These findings suggest that TikTok is an effective and engaging learning medium that supports vocabulary acquisition through its audiovisual features and enhances students’ motivation in learning English.